Evolving Automatic Speech Recognition (ASR) System on The Website for Learning to Facilitate English Speaking Practice - Fauzi, Iwan; Mardiana, Dina; Thomas, Orbit (Jurnal Ilmu Sosial Mamangan, 2025)
This study explores a product system for speech recognition, which is termed Automatic Speech Recognition (ASR), developed through research and development (R&D) method by adapting the ADDIE model (analysis, design, development, implementation, and evaluation). The product yielded through this research is an ASR system embedded into a website for the practice of speaking English as a foreign language (EFL) for students at the intermediate English level. Before the product was developed, researchers had conducted a need analysis to ensure that the product was needed as a learning support tool for English-speaking practice. After that, the feasibility of the product was measured through the evaluation of two independent experts from two fields of expertise: the expert of information and communication technology (ICT), and the expert of technology-enhanced language learning (TELL). Twenty-two EFL students were invited purposively to assess the ASR system during the trial to users. Results show that the ASR system proves to be a valuable educational tool, offering accessibility, usability, and interactive feedback that enhance user engagement and support language learning. However, this study has a significant problem, which is the inconsistency of speech recognition accuracy, particularly the speech from non-native speakers of English